A lithium-ion battery positive electrode superdispersant and its preparation method and application

By using a super dispersant containing phosphorus-containing esters, phenylcyclic ether-bonded organics and silane coupling agents in the positive electrode material of the lithium-ion battery, the problem of slurry inhomogeneity caused by the agglomeration of the positive electrode material is solved, and high efficiency is achieved The distribution and stability are improved significantly, which significantly improves the overall performance of the battery.

CN119315038BActive Publication Date: 2025-02-25SUZHOU DERBY ELECTRONIC MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411837338.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The particles of the positive electrode material of lithium-ion batteries are prone to agglomeration when preparing the slurry, resulting in a decrease in the uniformity and stability of the slurry and affecting the electrochemical performance of the battery. The existing dispersant is added in large amounts, which extrudes the content of the positive electrode material, which is not conducive to the improvement of battery energy density.

Method used

A lithium-ion battery positive electrode superdispersant is used, and its raw materials include solvent, a first component (phosphorus-containing ester organic substance), a second component (organic substance with benzene ring and ether bond) and an interface modifier (silane coupler ) By combining these components, the positive electrode particles can be effectively dispersed under a very small amount of addition (less than 0.2%), reducing the slurry viscosity, improving fluidity and dispersion uniformity.

Benefits of technology

Through the use of superdispersant, the overall performance of the battery can be significantly improved, including improving the solid content of the slurry, expanding the processing window, reducing the energy consumption of the electrode sheet drying, improving the consistency of the coating and interface uniformity, thereby improving the lithium-ion battery. energy density and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315038B_ABST
    Figure CN119315038B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium-ion battery positive electrode hyperdispersant and a preparation method and application thereof, belonging to the field of new material technology. The raw materials of the hyperdispersant of the present invention are composed of the following according to mass fractions: 50-80 parts of solvent, 10-20 parts of a first component, 5-15 parts of a second component, 1-10 parts of a small molecule amino acid, and 1-5 parts of an interface modifier; the first component contains at least one phosphorus-containing ester organic matter; the second component contains at least one benzene ring and an organic matter with an ether bond; the interface modifier is a silane coupling agent. The hyperdispersant of the present invention can effectively reduce the slurry viscosity, improve fluidity, and increase the slurry dispersion uniformity by adding less than 0.2%, thereby improving the overall performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a lithium ion battery positive electrode superdispersant, a preparation method and an application thereof. Background Art

[0002] As the global demand for clean and renewable energy continues to increase, lithium-ion batteries, as efficient and environmentally friendly energy storage devices, have been widely used in electric vehicles, portable electronic devices, energy storage systems, etc. In order to meet higher energy density, longer cycle life and better safety performance, the material science and technology of lithium-ion batteries continue to advance.

[0003] In the manufacturing process of lithium-ion batteries, the performance of positive electrode materials plays a vital role in the overall performance of the battery. Positive electrode materials are represented by lithium iron phosphate, which is usually composed of micron or nanometer particles. These particles are prone to agglomeration when preparing slurry, resulting in decreased uniformity and stability of the slurry. Agglomerated particles not only affect the density and conductivity of the electrode, but also reduce the transmission efficiency of lithium ions, thereby affecting the electrochemical performance of the battery.

[0004] In order to solve these problems, dispersants are widely used in the preparation process of positive electrode materials for lithium-ion batteries. The main function of dispersants is to improve the dispersion of particles and prevent agglomeration, thereby improving the stability and uniformity of the slurry. Common positive electrode dispersants include polyacrylic acid (PAA), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), etc. These dispersants effectively disperse particles to a certain extent through electrostatic repulsion, steric hindrance effect or a combination of the two, so that the positive electrode material remains in a good suspension state in the slurry.

[0005] However, the amount of such dispersants added is generally more than 0.2% of the solid component, which squeezes out the content of the positive electrode material and is not conducive to improving the battery energy density. In addition, with the development of material science, the particles of positive electrode materials are moving towards nanometer size, the proportion of carbon on the surface of the material is getting higher and higher, and the difficulty of dispersion is gradually increasing. Therefore, there is an urgent need for a super dispersant that can help solve the problem of difficult dispersion of positive electrode particles with a very small amount of addition. Summary of the invention

[0006] In view of the current problems of difficulty in dispersing positive electrode slurry of lithium ion batteries, easy agglomeration of carbon-coated main materials, too high slurry viscosity at high solid content, and poor coating effect, the present invention proposes a lithium ion battery positive electrode super dispersant and a preparation method and application thereof. By adding less than 0.2%, the slurry viscosity can be effectively reduced, the fluidity can be improved, and the slurry dispersion uniformity can be increased, thereby improving the overall performance of the battery.

[0007] The above purpose is achieved through the following technical solutions:

[0008] A lithium-ion battery positive electrode hyperdispersant, wherein the raw materials of the hyperdispersant are composed of the following components by mass: 50-80 parts of a solvent, 10-20 parts of a first component, 5-15 parts of a second component, 1-10 parts of a small molecule amino acid, and 1-5 parts of an interface modifier;

[0009] The first component contains at least one phosphorus-containing ester organic substance;

[0010] The second component contains an organic substance having at least one benzene ring and an ether bond;

[0011] The interface modifier is a silane coupling agent.

[0012] The solvent has the effect of dissolving and premixing the components of the hyperdispersant, but does not participate in the dispersion in actual applications. Commonly used polar organic solvents can be used. For example, the solvent is one of N,N-dimethylformamide (DMF), dimethylacetamide, N-methylpyrrolidone (NMP), acetonitrile, and methanol.

[0013] Due to the excellent solubility and chemical stability of N-methylpyrrolidone (NMP), preferably, the solvent is N-methylpyrrolidone (NMP).

[0014] The first component and the second component preferably have a molecular weight of 200-2000. If the molecular weight is too large, the viscosity will be too high during the homogenization process, the dispersing groups cannot fully play their role, and the dispersion efficiency will be reduced; if the molecular weight is too small, it will dissolve into the battery electrolyte, causing an increase in side reactions during the charge and discharge process and affecting the battery cycle life. At least 15% of the mass fraction of the first component and the second component combined is dissolved in NMP.

[0015] Preferably, the raw materials of the hyperdispersant are composed of the following parts by mass: 60-80 parts of solvent, 10-15 parts of the first component, 5-10 parts of the second component, 1-5 parts of small molecule amino acid, and 1-4 parts of interface modifier.

[0016] Preferably, the first component is a phosphorus-containing ester organic substance. The phosphorus-containing ester organic substance in the first component itself has a relatively high polarity and can be dissolved in polar organic solvents such as NMP. At the same time, the phosphate ester, phosphonate ester or phosphite ester around the phosphorus element has a phosphoric acid configuration and has good affinity with the main material of lithium iron phosphate or lithium manganese iron phosphate, and can quickly form an adsorption association on the surface of the main material particles. In the positive electrode slurry process, it can effectively penetrate between particles to form a steric hindrance effect, prevent the secondary agglomeration of particles in the slurry, and keep the viscosity of the slurry stable.

[0017] Preferably, the first component is at least one of tributyl phosphate, dibutyl phosphate, diphenyl isodecyl phosphite, lecithin, and (2-ethylhexyl) mono-2-ethylhexyl phosphate.

[0018] Preferably, the second component contains at least one benzene ring and an organic substance with an ether bond. The second component contains a benzene ring structure, and its large π bond has better affinity for the carbon material on the surface of the main material and the conductive agent, and can be better compatible and combined with the surface carbon-coated material, further helping to disperse and homogenize the particles in the slurry. The second component is at least one of alkylphenol polyoxyethylene ether, alkylphenol polyoxypropylene ether, bisphenol A diglycidyl ether, resorcinol diglycidyl ether, and o-phenylphenol glycidyl ether.

[0019] Preferably, the small molecule amino acid is at least one of alanine, glutamic acid, glycine, phenylalanine, isoleucine and aspartic acid. The small molecule amino acid is used to construct a buffer layer, which can adjust the pH value and increase the wettability of the main material and the conductive material surface, help the first component and the second component to wet and bond with the main material particle surface, and accelerate dispersion.

[0020] Preferably, the interface modifier is at least one of γ-aminopropyltriethoxysilane (KH-550), γ-glycidyloxypropyltrimethoxysilane (KH-560), octyltriethoxysilane (A-137), and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane. The interface modifier is an organic silane coupling agent. The silane coupling agent has a siloxane structure, which can undergo a hydrolysis reaction with water to generate silanols, and then react with hydroxyl groups on the surface of inorganic materials such as aluminum foil to form stable chemical bonds, consume water in the positive electrode slurry, and reduce the risk of positive electrode slurry gelation caused by water in the slurry and at the interface of contact with air. At the same time, the organic part interacts with the first component and the second component to help improve the interface contact, improve the dispersibility of the system, reduce the viscosity of the slurry, and improve the processing performance.

[0021] The present invention also provides a method for preparing a super dispersant for a positive electrode of a lithium ion battery. The specific steps are as follows:

[0022] Step 1: dissolving the first component in a solvent to form a solution A;

[0023] Step 2: dissolving the second component in solution A to form solution B;

[0024] Step 3: Mix the small molecule amino acid and solution B at 60°C to form solution C;

[0025] Step 4: After the temperature of solution C drops to room temperature, add the interface modifier dropwise while stirring to obtain the super dispersant.

[0026] The dissolution process of the first component and the second component needs to be mixed and stirred for 1-4 hours under argon protection conditions, and the temperature range is 25-50°C.

[0027] The small molecule amino acid, solution A and solution B need to be stirred and mixed evenly under argon protection for 1-2 hours.

[0028] The interface modifier is added dropwise under stirring conditions, and the mixing time is 0.5-1h.

[0029] The present invention also provides an application of the above-mentioned lithium ion battery positive electrode super dispersant, which is applied to lithium ion battery positive electrode slurry. Conventional lithium ion battery positive electrode slurry also includes positive electrode main material, conductive agent, binder and organic solvent; the positive electrode main material is one or more of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, sodium iron pyrophosphate, sodium vanadium sulfate, and sodium iron sulfate; the conductive agent is one or more of carbon black, acetylene black, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes, fullerene, conductive graphite, and graphene; the binder in the positive electrode slurry is polyvinylidene fluoride, and the organic solvent is N-methylpyrrolidone (NMP). The amount of the lithium ion battery positive electrode super dispersant used in the present invention is 0.01-0.2% of the mass of the solid component in the lithium ion battery positive electrode slurry.

[0030] The solid content of the lithium-ion battery positive electrode slurry is greater than 58% and less than 72%.

[0031] The lithium ion battery positive electrode hyperdispersant of the present invention is added during the homogenization process of the lithium ion battery positive electrode. Each component in the hyperdispersant can be affinity anchored on the corresponding material respectively, and the formation of steric hindrance is accelerated with the help of small molecules, which can quickly promote the uniform dispersion of lithium iron phosphate particles and conductive agents in the solvent, and effectively reduce the overall viscosity of the slurry. Under the same discharge viscosity, the solid content of the slurry can be increased by at least 5 percentage points, greatly reducing the use of organic solvents, and reducing the energy consumption of pole piece drying. The slurry has better viscosity retention ability, greatly improved coating consistency, and a uniform and stable interface.

[0032] The present invention also claims protection for a lithium-ion battery positive electrode plate, comprising a positive electrode current collector, wherein the positive electrode current collector is coated with the above-mentioned lithium-ion battery positive electrode slurry.

[0033] The lithium-ion battery positive electrode super dispersant provided in the present application is used in the process of lithium-ion battery positive electrode homogenization, which can improve the dispersion state between the positive electrode component particles, accelerate the surface wetting of the main material and conductive agent, etc., and efficiently disperse at a low addition amount, help reduce the viscosity of the positive electrode slurry and inhibit viscosity rebound, effectively improve the coating uniformity, improve the pole piece processing window, and help reduce costs and increase efficiency in the lithium battery positive electrode process.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. In the present invention, the dispersant can accelerate the wetting of the material surface, quickly achieve penetration and utilize the steric hindrance effect to disperse the various components of the slurry, and further consolidate the dispersion effect through small molecules and interface modification, thereby achieving stable slurry viscosity, thereby increasing the slurry solid content, expanding the processing window, and helping to reduce costs and increase efficiency in the positive electrode homogenization process.

[0036] 2. The amount of the dispersant added in the present invention is within 0.2%, the amount added is small and no special homogenization process or equipment is required during use. The effect of reducing viscosity and improving dispersion can be achieved by adding the dispersant of the present invention in a certain ratio on the basis of the existing homogenization scheme without the need for additional process cost investment.

[0037] 3. The dispersant of the present invention is suitable for a wide range of scenarios and has a significant dispersing effect on various types of main materials, conductive agents, and adhesives on the market.

[0038] 4. The conductive agent is dispersed more evenly in the positive electrode material, ensuring the uniform distribution of the conductive network and improving the overall conductivity of the electrode.

[0039] 5. Improve the interface properties between the positive electrode material and the foil, improve the distribution state of the adhesive, and improve the electrode peeling force and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The rheological curves of fresh slurry of lithium iron phosphate prepared by liquid phase method and after standing for 48 hours are shown in Examples 1-3 and Comparative Examples 1-3 of the present invention and a blank reference example;

[0041] Figure 2 The rheological curves of fresh slurry of lithium iron phosphate prepared by solid phase method and after standing for 48 hours are shown in Examples 1-3 and Comparative Examples 1-3 of the present invention and a blank reference example;

[0042] Figure 3 These are the rheological curves of fresh slurry of high specific surface area lithium manganese iron phosphate and the rheological curves after standing for 48 hours for Examples 1-3 of the present invention, Comparative Examples 1-3 and a blank reference example. DETAILED DESCRIPTION

[0043] The principles and characteristics of the present invention are described below in conjunction with the embodiments. It should be noted that the following examples are only used to explain the present invention and are not used to limit the present invention. Other combinations and various improvements within the concept of the present invention can be made without departing from the spirit or scope of the present invention.

[0044] Embodiment 1:

[0045] Weigh 10 parts of tributyl phosphate (i.e., the first component) by mass, with a molecular weight of 266.31, add it to 80 parts of N-methylpyrrolidone (NMP), continue stirring at 45°C under argon protection, and continue to add 5 parts of hexadecylphenol polyoxyethylene ether (i.e., the second component) with a molecular weight of 1638 after being completely dissolved for 1 hour, raise the temperature to 60°C, add 3 parts of aspartic acid (i.e., a small molecule amino acid), keep stirring after being completely dissolved and cool to room temperature. Add 2 parts of γ-aminopropyl triethoxysilane (KH-550) (i.e., an interface modifier) ​​dropwise, and continue stirring for 1 hour to obtain super dispersant Example 1.

[0046] Embodiment 2:

[0047] Weigh 15 parts of dibutyl phosphate (i.e., the first component) by mass, with a molecular weight of 210.21, add it to 73 parts of N-methylpyrrolidone (NMP), continue stirring at 40°C under argon protection, and continue to add 10 parts of hexadecylphenol polyoxyethylene ether (i.e., the second component) with a molecular weight of 1638 after being completely dissolved for 1 hour, raise the temperature to 60°C, add 1 part of phenylalanine (i.e., a small molecule amino acid), keep stirring after being completely dissolved and cool to room temperature. Add 1 part of γ-glycidyloxypropyltrimethoxysilane (KH-560) (i.e., an interface modifier) ​​dropwise, and continue stirring for 1 hour to obtain super dispersant Example 2.

[0048] Embodiment 3:

[0049] Weigh 20 parts of diphenyl isodecyl phosphite (i.e., the first component) by mass, with a molecular weight of 438.62, add it to 50 parts of N-methylpyrrolidone (NMP), continue stirring at 50°C under argon protection, and continue to add 15 parts of dodecylphenol polyoxypropylene ether (i.e., the second component) with a molecular weight of 842 after being completely dissolved for 1 hour, heat to 60°C, add 10 parts of phenylalanine (i.e., a small molecule amino acid), keep stirring after being completely dissolved and cool to room temperature. Add 5 parts of γ-aminopropyl triethoxysilane (KH-550) (i.e., an interface modifier) ​​dropwise, and continue stirring for 1 hour to obtain super dispersant Example 3.

[0050] Embodiment 4:

[0051] Weigh 15 parts of lecithin (i.e., the first component) by mass, with a molecular weight of 758.1, add it to 71 parts of N-methylpyrrolidone (NMP), continue stirring at 50°C under argon protection, and continue to add 10 parts of bisphenol A diglycidyl ether (i.e., the second component) with a molecular weight of 340.4 after it is completely dissolved for 1 hour, then heat it to 60°C, add 2 parts of isoleucine (i.e., a small molecule amino acid), keep stirring after it is completely dissolved and cool to room temperature. Add 2 parts of octyl triethoxysilane (A-137) (i.e., an interface modifier) ​​dropwise, and continue stirring for 1 hour to obtain super dispersant Example 4.

[0052] Embodiment 5:

[0053] Weigh 15 parts of (2-ethylhexyl) phosphate mono-2-ethylhexyl ester (i.e., the first component) by mass, with a molecular weight of 306.4, add it to 60 parts of N-methylpyrrolidone (NMP), continue to stir at 50°C under argon protection, and continue to add 15 parts of resorcinol diglycidyl ether (i.e., the second component) with a molecular weight of 222.24 after it is completely dissolved for 1 hour, heat it to 60°C, add 5 parts of glutamic acid (i.e., a small molecule amino acid), keep stirring after it is completely dissolved and cool it to room temperature. Add 5 parts of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane (i.e., an interface modifier) ​​dropwise, and continue to stir for 1 hour to obtain super dispersant Example 4.

[0054] Embodiment 6:

[0055] Weigh 10 parts of tributyl phosphate (i.e., the first component) by mass, with a molecular weight of 266.31, add it to 74 parts of N-methylpyrrolidone (NMP), continue stirring at 45°C under argon protection, and continue to add 10 parts of o-phenylphenol glycidyl ether (i.e., the second component) with a molecular weight of 226.27 after it is completely dissolved for 1 hour, then heat it to 60°C, add 3 parts of glycine (i.e., a small molecule amino acid), keep stirring after it is completely dissolved and cool to room temperature. Add 3 parts of γ-aminopropyl triethoxysilane (KH-550) (i.e., an interface modifier) ​​dropwise, and continue stirring for 1 hour to obtain super dispersant Example 6.

[0056] Comparative Example 1:

[0057] Without adding the first component, other conditions are the same as in Example 1, that is, 5 parts of hexadecylphenol polyoxyethylene ether (as the second component) are weighed by mass, and the molecular weight is 1638, and added to 80 parts of N-methylpyrrolidone (NMP), and stirred continuously at 45°C under argon protection environment, and after being completely dissolved for 1 hour, the temperature is raised to 60°C, and 3 parts of aspartic acid (i.e., small molecule amino acid) are added, and stirring is maintained after being completely dissolved and cooled to room temperature. 2 parts of γ-aminopropyltriethoxysilane (KH-550) (i.e., interface modifier) ​​are added dropwise, and stirring is continued for 1 hour to obtain the dispersant of Comparative Example 1.

[0058] Comparative Example 2:

[0059] Without adding the second component, other conditions are the same as those in Example 2, that is, 15 parts of dibutyl phosphate (i.e., the first component) are weighed by mass, and the molecular weight is 210.21, and added to 73 parts of N-methylpyrrolidone (NMP), and stirred continuously at 40°C under argon protection environment, and after being completely dissolved for 1 hour, the temperature is raised to 60°C, and 1 part of phenylalanine (i.e., a small molecule amino acid) is added, and stirring is maintained after being completely dissolved and cooled to room temperature. 1 part of γ-glycidyloxypropyltrimethoxysilane (KH-560) (i.e., an interface modifier) ​​is added dropwise, and stirring is continued for 1 hour to obtain the dispersant of Comparative Example 2.

[0060] Comparative Example 3:

[0061] No small molecule amino acid and interface modifier are added, and other conditions are the same as Example 3, that is, 20 parts of diphenyl isodecyl phosphite (i.e., the first component) with a molecular weight of 438.62 are weighed by mass, added to 50 parts of N-methylpyrrolidone (NMP), and stirred continuously at a temperature of 50° C. under an argon protection environment. After complete dissolution for 1 hour, 15 parts of dodecylphenol polyoxypropylene ether (i.e., the second component) with a molecular weight of 842 are added. After complete dissolution, stirring is maintained and the mixture is cooled to room temperature. After stirring is continued for 1 hour, the dispersant of Comparative Example 3 can be obtained.

[0062] Application Example 1:

[0063] The super dispersant obtained in Examples 1-6 and the dispersant obtained in Comparative Examples 1-3 were respectively applied to the positive electrode slurry of lithium iron phosphate (model DY-3 of Defang Nano). The positive electrode slurry of lithium iron phosphate (model DY-3 of Defang Nano) in the liquid phase process includes a positive electrode main material, a conductive agent, a binder and an organic solvent. The positive electrode slurry was prepared according to the mass ratio of lithium iron phosphate: carbon nanotubes: adhesive PVDF: dispersant: NMP = 97: 1: 2: 0.01: 47.06, and the solid content of the slurry was controlled to be stable at 68%. After the homogenization was completed, 6 groups of slurries containing Examples 1-6 and 3 groups of slurries containing Comparative Examples 1-3 were obtained. At the same time, a portion of slurry without dispersant was taken, that is, the positive electrode slurry was prepared according to the mass ratio of lithium iron phosphate: carbon nanotubes: adhesive PVDF: dispersant: NMP = 97: 1: 2: 0: 47.06 as a reference example. Anton Paar MCR102e rheometer was used to test the slurry just dispersed and the same slurry after standing for 48 hours. The rheological curve of the slurry was observed by changing the shear rate. The test results are shown in Figure 1 shown.

[0064] Figure 1 The rheological curves of fresh slurry of lithium iron phosphate prepared by liquid phase method and after standing for 48 hours are shown in Examples 1-3, Comparative Examples 1-3 and Reference Examples of the present invention;

[0065] Depend on Figure 1 It can be seen from the data that the positive electrode slurry used in Examples 1-3, whether in a fresh state or after standing for 48 hours, is better than the application of Comparative Examples 1-3, and is much better than the reference example, proving that the hyperdispersant of the present invention can effectively disperse lithium iron phosphate slurry, improve rheological properties, and expand the processing window. And after standing for 48 hours, the slurry viscosity does not rebound. The hyperdispersant of the present invention effectively inhibits the reagglomeration of the powder in the slurry system and has an excellent stabilizing effect on maintaining the slurry state.

[0066] The positive electrode slurry used in the above embodiment, comparative example and reference example was coated on aluminum foil and dried at 120°C for 45 minutes to obtain the corresponding positive electrode sheet. The peel strength of the sheet was tested and recorded using a universal tensile machine, and the sheet resistance was measured using an Atomic Energy BER2500 sheet resistance meter and the cracking of the sheet after coating was recorded. The test results are shown in Table 1:

[0067] Table 1: Corresponding positive electrode sheet peeling strength and sheet resistance obtained from fresh lithium iron phosphate slurry prepared by liquid phase process for Examples 1-3 of the present invention, Comparative Examples 1-3 and Reference Example

[0068] sample Electrode sheet resistance (Ω·cm) Pole state Peel strength (N / m) Reference example (blank) 5.237 Minor cracks 0.211 Example 1 2.375 Smooth without cracks 0.265 Example 2 2.411 Smooth without cracks 0.243 Example 3 2.882 Smooth without cracks 0.247 Example 4 2.771 Smooth without cracks 0.239 Example 5 2.754 Smooth without cracks 0.246 Example 6 2.672 Smooth without cracks 0.245 Comparative Example 1 3.557 Smooth without cracks 0.222 Comparative Example 2 3.687 Smooth without cracks 0.231 Comparative Example 3 4.197 Smooth without cracks 0.225

[0069] It can be seen from the data in Table 1 that, compared with Comparative Examples 1-3 and Reference Examples, after adding the hyperdispersant of the present invention, due to the better slurry dispersion effect, the conductive material and the binder can be spread on the electrode to a greater extent, and a more effective conductive path and bonding network are constructed, so the electrode resistance is greatly reduced and the peel strength is greatly improved. However, due to the uneven dispersion of the blank control group, cracks are easily formed in the electrode coating under high solid content, which further proves that the hyperdispersant of the present invention has a good dispersion effect on the positive electrode slurry.

[0070] Application Example 2:

[0071] The super dispersant obtained in Examples 1-6 and the dispersant obtained in Comparative Examples 1-3 are respectively applied to the positive electrode slurry of solid-phase lithium iron phosphate (model Y-9C of Hunan Yuneng). The solid-phase lithium iron phosphate (model Y-9C of Hunan Yuneng) positive electrode slurry includes a positive electrode main material, a conductive agent, a binder and an organic solvent. The positive electrode slurry is prepared according to the mass ratio of lithium iron phosphate: carbon nanotube: binder PVDF: dispersant: NMP = 97: 1: 2: 0.1: 47.06, and the solid content of the slurry is controlled to be stable at 68%. After the homogenization is completed, 6 groups of slurries containing the super dispersants obtained in Examples 1-6 and three groups of slurries containing the dispersants of Comparative Examples 1-3 are obtained. At the same time, a group of slurries without adding dispersants were prepared as reference examples. That is, the reference example prepared the positive electrode slurry according to the mass ratio of lithium iron phosphate: carbon nanotubes: adhesive PVDF: dispersant: NMP = 97:1:2:0:47.06, and the solid content of the slurry was controlled to be stable at 68%. After the preparation was completed, the Anton Paar MCR102e rheometer was used to test the slurry just dispersed and the same slurry after standing for 48 hours. The rheological curve of the slurry was observed by changing the shear rate. The test results are shown in Figure 2 shown.

[0072] Figure 2 The rheological curves of fresh slurry of lithium iron phosphate prepared by solid phase method and after standing for 48 hours are shown in Examples 1-3, Comparative Examples 1-3 and Reference Examples of the present invention;

[0073] Depend on Figure 2 It can be seen from the data that the positive electrode slurry used in Examples 1-3, whether in a fresh state or after standing for 48 hours, is better than the application of Comparative Examples 1-3, and is much better than the reference example, proving that the hyperdispersant of the present invention can effectively disperse lithium iron phosphate slurry, improve rheological properties, and expand the processing window. And after standing for 48 hours, the slurry viscosity does not rebound, and the hyperdispersant effectively inhibits the re-agglomeration of the powder in the slurry system, and has an excellent stabilizing effect on maintaining the slurry state.

[0074] The positive electrode slurry used in the above embodiment, comparative example and reference example was coated on aluminum foil and dried at 120°C for 45 minutes to obtain the corresponding positive electrode sheet. The peel strength of the sheet was tested and recorded using a universal tensile machine, and the sheet resistance was measured using an Atomic BER2500 sheet resistance meter and the cracking of the sheet after coating was recorded. The test results are shown in Table 2:

[0075] Table 2: Corresponding positive electrode sheet peeling strength and sheet resistance obtained from fresh lithium iron phosphate slurry prepared by solid phase process for Examples 1-6 of the present invention, Comparative Examples 1-3 and Reference Example

[0076] sample Electrode sheet resistance (Ω·cm) Pole state Peel strength (N / m) Reference example (blank) 7.835 Minor cracks 0.221 Example 1 4.425 Smooth without cracks 0.254 Example 2 4.456 Smooth without cracks 0.253 Example 3 4.811 Smooth without cracks 0.249 Example 4 4.802 Smooth without cracks 0.255 Example 5 4.911 Smooth without cracks 0.249 Example 6 4.784 Smooth without cracks 0.251 Comparative Example 1 6.532 Smooth without cracks 0.229 Comparative Example 2 5.437 Smooth without cracks 0.234 Comparative Example 3 6.143 Smooth without cracks 0.235

[0077] It can be seen from the data in Table 2 that the carbon content of lithium iron phosphate powder produced by the solid phase method is lower than that produced by the liquid phase method, so the overall resistivity is higher, but due to the smaller particle size, the overall peeling force is also higher after being matched with an adhesive. Compared with the control example and the reference example, after adding the super dispersant of the present invention to Examples 1-6, due to the better slurry dispersion effect, the conductive material and the adhesive can be spread on the electrode to a greater extent, and a more effective conductive path and bonding network are constructed, so the electrode resistance is greatly reduced and the peeling strength is greatly improved. It is further proved that the super dispersant of the present invention has a good dispersion effect on the positive electrode slurry.

[0078] Application Example 3:

[0079] The super dispersant obtained in Examples 1-6 and the dispersant obtained in Comparative Examples 1-3 are respectively applied to the high specific surface area lithium iron manganese phosphate (model: Xin Guorong LMFP64) positive electrode slurry. The high specific surface area lithium iron manganese phosphate (model: Xin Guorong LMFP64) positive electrode slurry includes a positive electrode main material, a conductive agent, a binder and an organic solvent. The positive electrode slurry is configured according to the mass ratio of lithium iron manganese phosphate: carbon nanotubes: adhesive PVDF: dispersant: NMP = 97: 1: 2: 0.2: 66.57, and the solid content of the slurry is controlled to be stable at 60%. After the homogenization is completed, 6 groups of slurries containing super dispersants of Examples 1-6 and three groups of slurries containing dispersants of Comparative Examples 1-3 are obtained. At the same time, a group of blank control examples are prepared, that is, the positive electrode slurry is configured according to the mass ratio of lithium iron manganese phosphate: carbon nanotubes: adhesive PVDF: dispersant: NMP = 97: 1: 2: 0: 66.57, and the solid content of the slurry is controlled to be stable at 60%. After the production is completed, the Anton Paar MCR102e rheometer is used to test the slurry just dispersed and the same slurry after standing for 48 hours. The rheological curve of the slurry is observed by changing the shear rate. The test results are shown in Figure 3 shown.

[0080] Figure 3The rheological curves of fresh slurry of high specific surface area lithium manganese iron phosphate and the rheological curves after standing for 48 hours are shown in Examples 1-3, Comparative Examples 1-3 and Reference Examples of the present invention;

[0081] Depend on Figure 3 It can be seen from the data that the positive electrode slurry used in Examples 1-3, whether in a fresh state or after standing for 48 hours, is better than the application of Comparative Examples 1-3, and is much better than the blank reference example, proving that the hyperdispersant of the present invention can effectively disperse lithium manganese iron phosphate slurry, improve rheological properties, and expand the processing window. And after standing for 48 hours, the slurry viscosity does not rebound, and the hyperdispersant effectively inhibits the re-agglomeration of the powder in the slurry system, and has an excellent stabilizing effect on maintaining the slurry state.

[0082] The positive electrode slurry used in the above embodiments, comparative examples and blank reference examples was coated on aluminum foil and dried at 120°C for 45 minutes to obtain the corresponding positive electrode sheet. The peel strength of the sheet was tested and recorded using a universal tensile machine, and the sheet resistance was measured using an Atomic Energy BER2500 sheet resistance meter and the cracking of the sheet after coating was recorded. The test results are shown in Table 3:

[0083] Table 3 shows the corresponding positive electrode sheet peeling strength and sheet resistance obtained in fresh slurry of lithium iron manganese phosphate with high specific surface area in Examples 1-6 of the present invention, Comparative Examples 1-3 and Reference Example

[0084] sample Electrode sheet resistance (Ω·cm) Pole state Peel strength (N / m) Reference example (blank) 4.221 Minor cracks 0.241 Example 1 1.902 Smooth without cracks 0.274 Example 2 1.93 Smooth without cracks 0.273 Example 3 2.31 Smooth without cracks 0.273 Example 4 2.22 Smooth without cracks 0.281 Example 5 2.27 Smooth without cracks 0.279 Example 6 2.13 Smooth without cracks 0.277 Comparative Example 1 2.85 Smooth without cracks 0.259 Comparative Example 2 2.947 Smooth without cracks 0.257 Comparative Example 3 3.255 Smooth without cracks 0.258

[0085] It can be seen from the data in Table 3 that, compared with the control example and the blank reference example, after adding the super dispersant of the present invention, the conductive material and the binder can be spread on the electrode to a greater extent due to the better slurry dispersion effect in Examples 1-6, and a more effective conductive path and bonding network are constructed, so the electrode resistance is greatly reduced and the peel strength is greatly improved. This further proves that the super dispersant of the present invention has a good dispersion effect on the positive electrode slurry.

[0086] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery positive electrode superdispersant, characterized in that The raw materials of the hyperdispersant are composed of the following parts by mass: 50-80 parts of solvent, 10-20 parts of the first component, 5-15 parts of the second component, 1-10 parts of small molecule amino acid, and 1-5 parts of interface modifier; The first component is at least one of tributyl phosphate, dibutyl phosphate, diphenyl isodecyl phosphite, lecithin, and (2-ethylhexyl) mono-2-ethylhexyl phosphate; The second component is at least one of alkylphenol polyoxyethylene ether, alkylphenol polyoxypropylene ether, bisphenol A diglycidyl ether, resorcinol diglycidyl ether, and o-phenylphenol glycidyl ether; The interface modifier is a silane coupling agent.

2. A lithium ion battery positive electrode superdispersant according to claim 1, characterized in that: The solvent is one of N,N-dimethylformamide, dimethylacetamide, N-methylpyrrolidone, acetonitrile and methanol.

3. A lithium ion battery positive electrode superdispersant according to claim 1, characterized in that: The small molecule amino acid is at least one of alanine, glutamic acid, glycine, phenylalanine, isoleucine and aspartic acid.

4. A lithium ion battery positive electrode superdispersant according to claim 1, characterized in that: The interface modifier is at least one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, octyl triethoxysilane, and N-(2-aminoethyl)-3-aminopropyl methyl diethoxysilane.

5. A method for preparing a lithium ion battery positive electrode superdispersant according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: Step 1: dissolving the first component in a solvent to form a solution A; Step 2: dissolving the second component in solution A to form solution B; Step 3: Mix the small molecule amino acid and solution B at 60°C to form solution C; Step 4: After the temperature of solution C drops to room temperature, add the interface modifier dropwise while stirring to obtain the hyperdispersant; Both step 1 and step 2 need to be mixed and stirred for 1-4 hours to dissolve under argon protection, and the temperature range is 25-50°C; step 3 needs to be stirred and mixed evenly under argon protection, and the mixing time is 1-2 hours; step 4 requires the mixing time of adding the interface modifier while stirring for 0.5-1 hour.

6. An application of the lithium ion battery positive electrode superdispersant according to any one of claims 1 to 4, characterized in that: The lithium ion battery positive electrode super dispersant is applied to the lithium ion battery positive electrode slurry, and the amount used is 0.01-0.2% of the mass of the lithium ion battery positive electrode solid component.

7. A positive electrode plate for a lithium-ion battery, comprising a positive electrode current collector, wherein the positive electrode current collector is coated with a positive electrode slurry formed by the positive electrode slurry of the lithium-ion battery according to claim 6.

Citation Information

Patent Citations

  • Positive electrode film layer additive composition, positive electrode film layer additive, positive electrode plate and secondary battery

    CN114050260A

  • Dispersing and softening agent for positive electrode slurry of lithium ion battery and application of dispersing and softening agent

    CN115863643A